Influence of Parity on Opting Optimal Season for Breeding in Murrah Buffaloes (Journal of Buffalo Science, 2017)
Environmental factors place a crucial role in reproductive management of buffaloes by regulating their estrous cycle. Conception occurs if breeding takes place in favorable season where availability of sufficient herbage and water. Influence of parity on selection of breeding seasonal, leads to conception, was not yet reported in murrah buffaloes. Therefore, the present investigation was carried out to analyse the influence of parity on selecting an optimal season for breeding among murrah buffaloes in south India. Sixty reproductively active murrah buffaloes belonged to southern part of Indian subcontinent were recruited in the study and grouped based on their parity. Estrus behaviour, date of mating and consequent pregnancy was recorded for every individual buffalo. A conception rate of 81.67% was achieved with natural mating. Among the 49 pregnant animals, 12 were nulliparous (n=19), 15 were primiparous (n=16) and 22 were multiparous (n=25). Conception rate was high during winter (32.65%), followed by autumn (26.53%), monsoon (20.41%) and pre-winter (20.41%). Major factors such as age, low reproductive efficiency during late winter and early autumn, delayed resumption after calving appears to affect the conception rate. Prolonged summer, extended from March to July, noticed in recent years decreases the duration of other seasons like spring and autumn. Effective breeding of nulliparous was witnessed on winter, primiparous during autumn and multiparous was scheduled from monsoon to pre-winter. The present study concludes that selection of optimal season for breeding was rather influenced by the parity of individual buffaloes.